Thyrotoxicosis leading to Renal Tubular Acidosis presenting as periodic paralysis - A case report - Sourya Sourabh Mohakuda1; Rajiv Pakhetra2; Naveen Yadav3 (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2019)
Periodic fl accid paralysis is related to loss of tone and power transiently and which occurs repeatedly over time. Etiologies like channelopathies, myasthenia gravis and thyroid disorders are common. There have been case reports of thyroid disorders leading to periodic paralysis. The pathophysiology attributed to it is the increased uptake of potassium by the cells in the thyrotoxic state. Thyrotoxicosis is also an uncommon cause for distal renal tubular acidosis. In our case, we present a case of thyrotoxicosis leading to distal RTA presenting as periodic paralysis. On correction of thyrotoxic state with radioactive iodine ablation the renal tubular acidosis remmited both clinically and on arterial blood gas analysis. We report this case as there are very few cases of such nature which are reported worldwide.